Natural Resource Extraction and Economic Performance of the Niger Delta Region in Nigeria - Fubara, Susan Amiesa; Iledare, Omowumi O.; Gershon, Obindah; Ejemeyovwi, Jeremiah (International Journal of Energy Economics and Policy, 2019)
The effect of natural resource extraction on regional and sub-national economic growth has only recently started to generate discussions in energy and regional economics literatures. This paper investigates this issue for the oil producing (Niger Delta) region in Nigeria using a panel data modelling framework. Empirical results from the analysis show no significant relationship between direct extractive activities on the internally generated revenue of each state. However, there is strong statistical evidence that show extractive activities impact positively on the total state level revenue - in the form of production-based derivation fund that accrues to oil producing states. In addition, the extractive activities positively and significantly affect each state’s gross domestic product and its disaggregated industries (petroleum and services). However, the impact of the natural resource extraction on the non-oil industry (manufacturing) is negative and not statistically significant. So, the results obtained renders inconclusive, the argument of a possible existence of the “resource curse” at the subnational level in Nigeria. Conclusively, natural resource extraction has positive significant impact on the economic performance of states in the oil-producing region, in contrast to the negative impact at the national level. The results bring to the fore, the need for diversification away from oil to other sectors – especially in within petroleum resource-rich regions/states of the Nigeria. The outcome of the study further highlights another policy issue of better managing oil-resource revenues towards achieving national economic goals including SDGs. Keywords: Crude Oil Extraction, Economic Performance, Niger Delta, Panel Data, Regression Modelling, Nigeria JEL Classifications: Q32, Q35, R11, R15 DOI: https://doi.org/10.32479/ijeep.7716